Concentração sérica da proteína C reativa como indicador preditivo do prognóstico clínico em indivíduos com hemorragia subaracnóidea aneurísmática - Romero, Flávio Ramalho [UNESP] (2014)
Introduction: Cerebral vasospasm is a prolonged constriction in arteries of subarachnoid space. It is the main cause of morbidity after subarachnoid hemorrhage (SAH). The objective was to study the relationships between C-reactive protein levels and clinical outcome and the development of cerebral vasospasm after aneurismal SAH. METHOD: One hundred adult patients with aneurismal SAH were prospectively evaluated. Glasgow Coma Scale (GCS) score, Hunt and Hess grade, Fisher grade, CT scans, digital subtraction angiography studies, transcranial doppler (TCD) and daily neurological examinations were recorded. Serial serum C reactive protein (CRP) measurements were evaluated daily from the admission to the 10th day. Glasgow Outcome Scale (GOS) and the modified Rankin Scale (mRS) were used to predict the outcome. RESULTS: There was progressive increase in the CRP levels from the admission to 3rd postictal day, followed by slow decrease until the 9th day. Hemodynamic changes in TCD were associated with higher serum CRP levels (correlation coefficient methodology; z = 8.381, p < 0.0001, r = 0,86). Clinical vasospasm patients showed the highest serum CRP levels (correlation coefficient methodology; z = 7.863, p < 0.0001, r = 0,74). Patients with lower GCS scores presented with increased CRP levels (correlation coefficient methodology; z = -8.712, p < 0.0001, r = -0,87). Low admission GCS scores were inversely correlated with high serum CRP levels. Patients with higher Hunt and Hess grades on admission presented significantly higher CRP serum levels (correlation coefficient methodology; z = 6.842, p < 0.0001, r = 0,80) Similarly, patients with higher admission Fisher grades showed increased levels of CRP (correlation coefficient methodology; z = 7.789, p < 0.0001, r = 0,84). In regard to their GOS scores, patients with higher CRP serum levels presented less favorable outcomes (correlation coefficient methodology ...